Science, physics and astronomy in schools and communities: experience report - Pereira, Cyntia Cristina; Pereira, Lázaro Trancoso; Benincá, Thalita Sartori (Cadernos de Astronomia, 2024)
This article aims to analyze the Extension Project ’’Science, Physics and Astronomy in Schools and for Communities’’, aimed at communities and elementary and high school students in Domingos Martins, ES. In a critical and reflective way, based on the results achieved, its purpose, methodology, history and insertion in the context of scientific education in the state of Espírito Santo are proposed. It is concluded that the project has the potential to establish a great connection between communities, schools and the Federal University of Espírito Santo (UFES), in addition to providing benefits to the local scientific culture